PEMANFAATAN RIMPANG JAHE MERAH (Zingiber officinale Roscoe) SEBAGAI BIOREDUKTOR DALAM PEMBUATAN NANOPARTIKEL EMAS DAN PENAMBAHAN CARBOXY METHYL CELLULLOSE NATRIUM (CMC-Na) SEBAGAI STABILISATOR - Titta Hartyana Sutarna; Hestiary Ratih; Arie Hardian; Dwi Ayudhaningsih (Jurnal Tadris Kimiya, 2026)
Green synthesis of gold nanoparticles (AuNPs) using plant extracts has attracted increasing attention as an environmentally benign alternative to conventional chemical methods. However, achieving controlled particle size and long-term colloidal stability remains a significant challenge. This study investigated the potential of red ginger (Zingiber officinale Roscoe) rhizome extract as a bioreducing agent for gold-containing colloidal particle formation and evaluated the stabilizing effect of sodium carboxymethyl cellulose (CMC-Na). The extract was characterized through antioxidant and phytochemical analyses before being employed to reduce HAuCl₄. The resulting colloidal systems were analyzed using UV–Vis spectroscopy, polarized microscopy, particle size analysis, zeta potential measurement, and storage stability evaluation. The appearance of a purple-colored dispersion with surface plasmon resonance bands at 550–557.5 nm indicated the formation of gold-containing colloidal particles. Initial particle sizes ranged from 137 to 233.4 nm, with larger particles observed at higher extract concentrations, suggesting concentration-dependent particle growth or aggregation. Phytochemical constituents containing hydroxyl, carbonyl, and carboxyl functional groups are proposed to facilitate Au³⁺ reduction and contribute to the initial capping of the particles. Among the tested formulations, 2% CMC-Na provided the greatest improvement in short-term colloidal stability, delaying aggregation for approximately 14 days. Nevertheless, the substantial increase in hydrodynamic diameter during storage indicates the formation of aggregated or polymer-coated colloidal structures rather than well-dispersed AuNPs. These findings demonstrate the feasibility of red ginger extract for green gold colloid synthesis while highlighting the need for further optimization and advanced characterization to achieve smaller, more uniform, and long-term stable AuNPs.